FRI0369 Neurotrophins are involved in vascular remodelling of giant cell arteritis. (23rd January 2014) - Ly, K. H.; Régent, A.; Sindou, P.; Le-Jeunne, C.; Brezin, A.; Witko-Sarsat, V.; Labrousse, F.; Fauchais, A.-L.; Vidal, E.; Mouthon, L.; Jauberteau-Marchan, M.-O.
Abstract : Background: Giant cell arteritis (GCA) is characterized by intimal hyperplasia leading to ischemic manifestations involving extra-cranial branches of carotid arteries and aorta. The pathogenesisof GCA is poorly understood. Neurotrophins (NT) and their receptors (NTR), are protein factors for differentiation and survival of neurons. We distinguish the nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin 3 (NT-3) and neurotrophin 4/5 (NT-4/5). NT produce their effects by interacting with receptors: the selective tropomyosin receptor kinase (Trk) (TrkA, TrkB and TrkC) and a non-selective receptor p75NTR. NT and NTR are also involved in the proliferation and migration of endothelial cells and in the migration of vascular smooth muscle cells (VSMC). Objectives: We hypothetized that neurotrophins are involved in vascular remodelling of GCA. Methods: We included consecutive patients who underwent temporal artery biopsy (TAB) for a suspicion of GCA. VSMC were cultured from TAB. We selected four patients with biopsy proven GCA and four patients with another diagnosis that GCA (controls). Protein expression of NT and NTR were determined by immunohistochemistry on paraffin-embedded temporal arteries. Immunostaining intensities were quantified. NT and NTR mRNA extracted from VSMC were measured by quantative real-time reverse transcription-PCR. Enzyme-linked immunosorbent assay Kit were used to measure concentrations of NGF and BDNF in serum. Cell proliferation assay was assessed by BrdU incorporation. All experiments were performed with primers and antibodies against NGF, BDNF, NT3, TrkA, TrkB, TrkC, and p75NTR. Exogenous BDNF was used for proliferation assay. Results: Temporal arteries of GCA patients (n=22) and controls (n=20) showed immunoreactivity for NGF, BDNF, and TrkB, whereas only GCA patients showed immunoreactivity for NT3 and P75NTR. Immunostaining was more intense in GCA patients for NGF in the media (p=0.005) and adventitia (p=0.01) and for BDNF in the intima (p=0.04) and media (p=0.008). No significant difference was found for serum NGF and BDNF concentrations between GCA patients (n=28) and controls (n=48). An increase in VSMC expression of BDNF and TrkB transcripts was observed in GCA patients compared with controls with a significant difference for TrkB (Fold difference > 2). Exogenous BDNF appears to decrease proliferation of VSMC in GCA patients as compared to controls. Conclusions: Our results suggest that NT and NTR are involved in the vascular remodelling of GCA particularly BDNF and his receptors. In VSMC, BDNF can bind either TrkB or P75NTR. TrkB signalling rather promotes cell survival whereas p75NTR leads rather to apoptosis. In GCA patients BDNF seems to bind rather to p75NTR. This pro-apoptotic pathway could be activated to supply ischemic effects in patients with GCA. Further experiments performed on larger number of VSMC samples will be needed to confirm these results. Disclosure of Interest : None Declared